Experimental studies on a desalination plant using ocean temperature difference. (20th November 2007) - Abraham, Raju
A desalination plant of 100 m? per day capacity utilising the thermocline across the ocean depth was commissioned in Kavaratti Island, India during May 2005 and it is operational till date. The flash evaporation of warm surface seawater is followed by the condensation of vapour utilising deep-sea cold water. The plant draws water from 330 m depth at 12?C. A 1 MLD capacity floating plant was demonstrated during April?May 2006 off Chennai. Deep sea cold water was drawn to the barge from a depth of 620 m at 10.2?C using a High Density Poly Ethylene (HDPE) pipe of 1000 mm diameter suspended vertically. The surface seawater at 30?C was flash-evaporated inside the flash chamber positioned at about 10.5 m from the sea level for gravity flow. The generated vapour from the flash chamber was admitted to a shell and tube condenser in which the cooling medium is cold water. Aluminium tubes were used in the condenser at an inclination of 5? to prevent the tube inundation during the condensation. A booster-assisted water ring vacuum pump was used to generate the vacuum of 22?30 mbar. The floating plant was in operation for about 22 days and several parametric studies were carried out. Heat transfer and hydraulic characteristics of the system were studied. The paper discusses the technical studies on the desalination plant.